2012
DOI: 10.1080/10942912.2010.513216
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Characterization of Peroxidase from Sweet Gourd (Cucurbita moschataLam. Poiret)

Abstract: Peroxidase (EC 1.11.1.7; donor: hydrogen peroxide oxidoreductase) is an oxidoreductase enzyme found in many fruits and vegetables. This enzyme was purified from sweet gourd (Cucurbita moschata Lam. Poiret) by ammonium sulphate precipitation and CM-Sephadex ion-exchange chromatography. Furthermore, optimum pH, optimum temperature, optimum ionic strength, stable pH, and stable temperature conditions were determined as 7.2, 50 • C, 0.4 M, 8.0, and 40 • C, respectively. The molecular weight (M W ) of the enzyme wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
43
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 27 publications
0
43
0
Order By: Relevance
“…They were frequently isolated from red algae of the family Rhodomelaceae and had some important biological activities [53][54][55] . It was reported that the bromophenol derivatives coordinate to the active site Zn 2+ and to block the reaction catalysis.…”
Section: Resultsmentioning
confidence: 99%
“…They were frequently isolated from red algae of the family Rhodomelaceae and had some important biological activities [53][54][55] . It was reported that the bromophenol derivatives coordinate to the active site Zn 2+ and to block the reaction catalysis.…”
Section: Resultsmentioning
confidence: 99%
“…Then, the purification process was realised. The protein flow in the column effluents was determined spectrophotometrically at 280 nm as previously reported [64][65][66] . Both isoenzymes purities were controlled by sodium dodecyl sulphate-polyacrylamide gel electrophoresis (SDS-PAGE) according to Laemmli's method 67 .…”
Section: Ca Inhibitionmentioning
confidence: 99%
“…Then, supernatant was transferred to the previously prepared Sepharose-4B-L-tyrosine-sulphanilamide affinity column 50 . Subsequently, the proteins from the column were spectrophotometrically determined at 280 nm [79][80][81][82][83][84][85] . For determination of the purity of the hCA isoenzymes, sodium dodecyl sulphate-polyacrylamide gel electrophoresis (SDS-PAGE), having 10 and 3% acrylamide as an eluent and packing gel, respectively, with 0.1% SDS [86][87][88][89][90] , was performed, through which a single band was observed for each isoenzyme.…”
Section: Biochemical Studiesmentioning
confidence: 99%